Altered phobic reactions in frontotemporal dementia: A behavioural and neuroanatomical analysis. (September 2020) - Jimenez, Daniel A.; Bond, Rebecca L.; Requena-Komuro, Mai-Carmen; Sivasathiaseelan, Harri; Marshall, Charles R.; Russell, Lucy L.; Greaves, Caroline; Moore, Katrina M.; Woollacott, Ione OC.; Shafei, Rachelle; Hardy, Chris JD.; Rohrer, Jonathan D.; et al.
Abstract: Introduction: Abnormal behavioural and physiological reactivity to emotional stimuli is a hallmark of frontotemporal dementia (FTD), particularly the behavioural variant (bvFTD). As part of this repertoire, altered phobic responses have been reported in some patients with FTD but are poorly characterised. Methods: We collected data (based on caregiver reports) concerning the prevalence and nature of any behavioural changes related to specific phobias in a cohort of patients representing canonical syndromes of FTD and Alzheimer's disease (AD), relative to healthy older controls. Neuroanatomical correlates of altered phobic reactivity were assessed using voxel-based morphometry. Results: 46 patients with bvFTD, 20 with semantic variant primary progressive aphasia, 25 with non-fluent variant primary progressive aphasia, 29 with AD and 55 healthy age-matched individuals participated. Changes in specific phobia were significantly more prevalent in the combined FTD cohort (15.4% of cases) and in the bvFTD group (17.4%) compared both to healthy controls (3.6%) and patients with AD (3.5%). Attenuation of phobic reactivity was reported for individuals in all participant groups, however new phobias developed only in the FTD cohort. Altered phobic reactivity was significantly associated with relative preservation of grey matter in left posterior middle temporal gyrus, right temporo-occipital junction and right anterior cingulate gyrus, brain regions previously implicated in contextual decoding, salience processing and reward valuation. Conclusion: Altered phobic reactivity is a relatively common issue in patients with FTD, particularly bvFTD. This novel paradigm of strong fear experience has broad implications: clinically, for diagnosis and patient well-being; and neurobiologically, for our understanding of the pathophysiology of aversive sensory signal processing in FTD and the neural mechanisms of fear more generally.